2020
DOI: 10.1007/s00170-020-06174-0
|View full text |Cite
|
Sign up to set email alerts
|

Modal characterization of additively manufactured TPMS structures: comparison between different modeling methods

Abstract: The use of lattice structures has received increasing interest in various engineering applications owing to their high strength to weight ratio. Advances in additive manufacturing technologies enabled the manufacturing of highly complex lattice structures such as triply periodic minimal surface (TPMS) models in recent years. The application of simulation tools is expected to enhance the performance of these designs further. Therefore, it is vital to understand their accuracy and computational efficiency. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 30 publications
3
26
0
Order By: Relevance
“…Other failure modes, such as face wrinkling and core failure, can be prevented by increasing the relative density. These results agree with those of other studies [ 26 , 37 ] showing that increasing the thickness of the face sheets or using a tougher material can decrease the face normal stress and bond stress, which can prevent both failure modes.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Other failure modes, such as face wrinkling and core failure, can be prevented by increasing the relative density. These results agree with those of other studies [ 26 , 37 ] showing that increasing the thickness of the face sheets or using a tougher material can decrease the face normal stress and bond stress, which can prevent both failure modes.…”
Section: Resultssupporting
confidence: 92%
“…Many studies have demonstrated that discretising the core surface as a shell rather than a solid mesh produces superior results. This is because the thickness aspect ratio is large, and the shell model can provide more accurate results [ 26 , 27 , 28 ]. To generate the shell model, the software Rhino was used to generate TPMS geometries, which were then exported to ANSYS for finite element analysis (FEA) of the structure.…”
Section: Numerical Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…This theory was verified by numerous studies with both simulations and experiments. In fact, with at least 4 layers, the Primitive structure could receive its micromechanics properties including strength and elastic modulus [39]. A similar tendency can be found in the maximum midpoint displacement responses.…”
Section: Influences Of Tpms Propertiessupporting
confidence: 55%
“…The equivalent entity method is well established in the literature [41], to address the challenges (in consideration of the computation time and accuracy) arise from the complex porous FE modeling. Published literature [42] has confirmed the validity of such method in analyzing the dynamic properties of complex porous structures. Stress-mapping method [43] was used (see Figure S5) to achieve balanced simulation accuracy and computational speed.…”
Section: Fe Simulationmentioning
confidence: 80%